Facile Synthesis of Highly Conductive Platinum Nanofiber Mats as Conducting Core for High Rate Redox Supercapacitor - Choi, Seung-Hoon; Hyun, Tae-Seon; Lee, Hyejin; Jang, Sung-Yeon; Oh, Seong-Geun; Kim, Il-Doo (ELECTROCHEMICAL SOC INC, 2010)
We report the fabrication and characterization of conductive Pt fiber mats as the conducting core of a high rate redox supercapacitor. Electrospun Pt fiber mats calcined at 350 degrees C exhibited a high electrical conductivity of 412 S cm(-1) as well as highly porous morphologies composed of 10 nm crystalline Pt nanoparticles. The Pt fiber mats served as the conducting core for electrochemically deposited hydrous RuO(2) overlayers. The hybrid electrode utilizing hydrous RuO(2)-coated Pt fiber mats showed a high specific capacitance of similar to 409.4 F g(-1) and high rate capability with a capacity loss of only 21.4% from 10 to 1000 mV s(-1). (C) 2010 The Electrochemical Society. [DOI: 10.1149/1.3369539] All rights reserved.
Keywords: RUTHENIUM OXIDE; ENERGY-STORAGE